2011
DOI: 10.1002/art.30373
|View full text |Cite
|
Sign up to set email alerts
|

Atacicept in patients with rheumatoid arthritis and an inadequate response to tumor necrosis factor antagonist therapy: Results of a phase II, randomized, placebo-controlled, dose-finding trial

Abstract: Objective. To assess the efficacy, safety, and biologic activity of atacicept in patients with rheumatoid arthritis (RA) in whom the response to treatment with tumor necrosis factor antagonists was inadequate.Methods. The Atacicept for Reduction of Signs and Symptoms in Rheumatoid Arthritis Trial (AUGUST I) was a multicenter, phase II, double-blind, placebo-controlled dose-finding study involving 256 patients randomized 1:1:1:1 to receive atacicept (25 mg, 75 mg, or 150 mg) or placebo twice weekly for 4 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 42 publications
(50 reference statements)
7
84
0
4
Order By: Relevance
“…Overall, dose loading had no effect on the clinical outcomes or pharmacodynamics. A separate phase II dose-finding study of atacicept in patients with RA and an inadequate response to TNF antagonists (the AUGUST I study) also showed no significant beneficial effect on clinical measures of disease, including the primary end point, the ACR20-CRP (20,21). However, potent dose-dependent biologic activity was observed in that study (20,21).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Overall, dose loading had no effect on the clinical outcomes or pharmacodynamics. A separate phase II dose-finding study of atacicept in patients with RA and an inadequate response to TNF antagonists (the AUGUST I study) also showed no significant beneficial effect on clinical measures of disease, including the primary end point, the ACR20-CRP (20,21). However, potent dose-dependent biologic activity was observed in that study (20,21).…”
Section: Discussionmentioning
confidence: 97%
“…The reason for these differential responses is not clear. One possible explanation is selective mobilization of plasma cells into the circulation during treatment (i.e., weeks [16][17][18][19][20][21][22][23][24][25][26]. Another possibility is that this could result from rapid transition of mature B cells into plasma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, atacicept at the dosage employed in this clinical trial reduced the level of several biomarkers that are known to drive the progression of RA without showing clinical efficacy at the lowest ACR criteria for an effective clinical response to an experimental therapy. In the other clinical investigation [185], atacicept also was found to reduce total immunoglobulin and RF levels, but failed to alter anti-citrullinated protein antibody levels. The reduction in the levels of IgG-and IgA-RF in response to atacicept was more significant than the response of total IgG and IgA levels to the drug.…”
Section: Apoptotic Responses To Anti-ra Therapiesmentioning
confidence: 93%
“…Phase Ib placebo-controlled trial displayed biological activity of Atacicept in abating Ig levels and reducing total B cell numbers, in a dose-dependent manner [190]. Two phase II RCT of Atacicept in treating refractory rheumatoid arthritis displayed a rapid and profound decline of Ig and rheumatoid factor levels as well as circulating mature B cells and plasma cells in Atacicept group, although the primary endpoint of ACR20 was not met [191,192]. The biologic effects justify clinical trials in SLE.…”
Section: Ataciceptmentioning
confidence: 99%